2008
DOI: 10.3168/jds.2007-0256
|View full text |Cite
|
Sign up to set email alerts
|

Feeding High Proportions of Barley Grain Stimulates an Inflammatory Response in Dairy Cows

Abstract: The objective of this study was to evaluate effects of feeding increasing proportions of barley grain on acute phase response in lactating dairy cows. Eight cannulated primiparous (60 to 140 d in milk) Holstein dairy cows were assigned to 4 diets in a 4 x 4 Latin square experimental design. The experimental period lasted for 21 d, with 11 d of adaptation and 10 d of measurements. Cows were fed the following diets: 1) no barley grain in the diet, 2) 15% barley grain, 3) 30% barley grain, and 4) 45% barley grain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
224
5
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(248 citation statements)
references
References 21 publications
18
224
5
1
Order By: Relevance
“…Acidosis presents a particular danger (Guo et al, 2013), since it involves overproduction of volatile fatty acids and lactic acid. This mainly results in a decrease in rumen fluid pH, and the results of some authors studies (Emmanuel et al, 2008) also indicate the degradation of gram-negative bacteria. During the disintegration of the cell walls they release significant amounts of lipopolysaccharides affecting lipid metabolism, which leads to reduced triglycerides accumulation in the liver (Feingold et al, 1992).…”
Section: Oxidative Stress In Ruminantsmentioning
confidence: 99%
“…Acidosis presents a particular danger (Guo et al, 2013), since it involves overproduction of volatile fatty acids and lactic acid. This mainly results in a decrease in rumen fluid pH, and the results of some authors studies (Emmanuel et al, 2008) also indicate the degradation of gram-negative bacteria. During the disintegration of the cell walls they release significant amounts of lipopolysaccharides affecting lipid metabolism, which leads to reduced triglycerides accumulation in the liver (Feingold et al, 1992).…”
Section: Oxidative Stress In Ruminantsmentioning
confidence: 99%
“…New research conducted by our team and others has shown that feeding cows high proportions of concentrate in the diet is associated with major changes in the rumen ecosystem and lower ruminal pH (Emmanuel et al, 2008;Khafipour et al, 2009). The latter authors induced sub-acute rumen acidosis (SARA) in dairy cows using a grain-or a forage pellet-based diet.…”
Section: High-grain/low-forage Diets and Microbiotamentioning
confidence: 99%
“…Indeed, in early lactation dairy cows, the most important contributory factor in the increase of concentration of endotoxin in the rumen fluid is the abrupt dietary shifts towards diets containing greater energy density at the onset of lactation (Emmanuel et al, 2008;Khafipour et al, 2009). Free endotoxin is released in the rumen fluid during lysis of Gram-negative bacteria (Nagaraja et al, 1978).…”
Section: Sources and Translocation Of Endotoxin In Dairy Cowsmentioning
confidence: 99%
“…Repeated bouts of rumen acidosis can damage the surface of the rumen wall, allowing bacteria and toxins produced by bacteria to enter the portal circulation and invoke an inflammatory response (Gozho et al 2005). These translocated endotoxins stimulate the release of pro-inflammatory cytokines, resulting in enhanced secretion of acute phase proteins (Emmanuel et al 2008). Khafipour et al (2009) evaluated the effect of sub-acute ruminal acidosis on the concentrations of some acute phase proteins in dairy cows, and observed increased values of SAA, Hp and lipopolysaccharide-binding protein during the challenge.…”
Section: Acute Phase Proteins In Metabolic Diseasesmentioning
confidence: 99%